Discussing gender. Notes for a reflection on gender violence in college - Lozano Hernández, Abel (2015)
This paper presents some instances of gender violence on one of the Benemérita Universidad Autónoma de Puebla (BUAP) campuses. The information gathered in the field has led us to reflect on the processes and mechanisms used by individuals to face, on a daily basis, gender schemas that have been socially apprehended and are expressed in daily college life. This paper is based on the assumption that gender violence is structural and that its multiple concrete and symbolic expressions are constantly manifested in the exercise of power and in the production and reproduction of cultural patterns of being a man or a woman. Confronted with such a complex phenomenon, we propose an approach that allows us to distance ourselves from the dominant view that relates gender violence to the type of violence exercised only on women and to show how we all are subject to gender as a primary power relationship.